Drought effects on invertebrate metapopulation dynamics and quasi‐extinction risk in an intermittent river network. (15th June 2021) - Sarremejane, Romain; Stubbington, Rachel; England, Judy; Sefton, Catherine E. M.; Eastman, Michael; Parry, Simon; Ruhi, Albert
Abstract: Ecological communities can remain stable in the face of disturbance if their constituent species have different resistance and resilience strategies. In turn, local stability scales up regionally if heterogeneous landscapes maintain spatial asynchrony across discrete populations—but not if large‐scale stressors synchronize environmental conditions and biological responses. Here, we hypothesized that droughts could drastically decrease the stability of invertebrate metapopulations both by filtering out poorly adapted species locally, and by synchronizing their dynamics across a river network. We tested this hypothesis via multivariate autoregressive state‐space (MARSS) models on spatially replicated, long‐term data describing aquatic invertebrate communities and hydrological conditions in a set of temperate, lowland streams subject to seasonal and supraseasonal drying events. This quantitative approach allowed us to assess the influence of local (flow magnitude) and network‐scale (hydrological connectivity) drivers on invertebrate long‐term trajectories, and to simulate near‐future responses to a range of drought scenarios. We found that fluctuations in species abundances were heterogeneous across communities and driven by a combination of hydrological and stochastic drivers. Among metapopulations, increasing extent of dry reaches reduced the abundance of functional groups with low resistance or resilience capacities (i.e. low ability to persist in situ or recolonize from elsewhere, respectively). Our simulations revealed that metapopulation quasi‐extinction risk for taxa vulnerable to drought increased exponentially as flowing habitats contracted within the river network, whereas the risk for taxa with resistance and resilience traits remained stable. Our results suggest that drought can be a synchronizing agent in riverscapes, potentially leading to regional quasi‐extinction of species with lower resistance and resilience abilities. Better recognition of drought‐driven synchronization may increase realism in species extinction forecasts as hydroclimatic extremes continue to intensify worldwide. Abstract : Local community stability scales up regionally if heterogeneous landscapes maintain spatial asynchrony across discrete populations (hypothesis [H]1–H2)—but not if large‐scale stressors synchronize environmental conditions and biological responses (H3). We hypothesized that droughts decrease the stability of aquatic invertebrate metapopulations both by filtering out poorly adapted species locally, and by synchronizing their dynamics across a river network (H3). We tested this hypothesis using long‐term data describing invertebrate communities and hydrological conditions in a temperate river network. Our results suggest that drought can be a synchronizing agent in riverscapes, potentially leading to regional quasi‐extinction of species with low resistance and resilience abilities.